The Silent Epidemic: Understanding Osteosarcopenia and Its Impact on Elderly Health - Adi Kunti, Desak Putu Sukasanti; Putu Putrawan, Ida Bagus (CV. Publikasi Indonesia, 2025)
The occurrence of osteoporosis and sarcopenia often increases in the elderly population, yet it frequently does not present clear complaints. Osteoporosis is characterized by low bone mass and damage to the microarchitectural structure of bone, while sarcopenia refers to the loss of muscle mass, strength, and function. When both conditions coinside, the term used is osteosarcopenia. The presence of osteosarcopenia can increase the risk of falls, which may lead to fractures. Falls have a significant impact, both on individuals—including a decline in quality of life, the need for care in nursing homes, and even death—and on society, which faces rising healthcare costs. The purpose of this writing is to raise awareness about osteosarcopenia, which often receives insufficient attention, by providing an overview of this condition. With a better understanding, it is hoped that effective preventive measures can be taken to reduce the negative impacts caused by osteosarcopenia.